Arabic Sounds, Their Articulation Points, and Characteristics Between Ancient and Modern Speeches (Journal of the College of Basic Education, 2025)
The Arabic language is the language of the Holy Quran. It is a rich and precise language in the pronunciation of letters and their articulation points. This research is a study of the articulation points and characteristics of letters in the Arabic language. It addresses the differences between ancient and modern speakers, and reveals the reasons for the disagreement. It identifies several factors, including the development of some sounds over the years, as well as the difference in methodologies in studying characteristics. The difference in concepts has reinforced the disagreement between the two groups.